PWE-104 Gamma-glutamyl transferase but not markers of hepatic fibrosis is associated with cardiovascular disease in older people with type 2 diabetes mellitus: the edinburgh type 2 diabetes study. (22nd June 2015) - Morling, J; Fallowfield, J; Williamson, R; Robertson, C; Glancey, S; Guha, I; Strachan, M; Price, J
Abstract : Introduction: Patients with chronic liver disease (CLD) and, in particular, non-alcoholic fatty liver disease (NAFLD) are known to have both higher all-cause mortality and cardiovascular (CV) mortality rates than the general population. Beyond investigation of GGT there has been little exploration of the relationship between CV disease (CVD) and other markers of liver disease (non-specific liver injury, steatosis, steatohepatitis, liver fibrosis or portal hypertension). We examined the association of prevalent and incident CV disease with CLD in a cohort of community-based people with type 2 diabetes (T2DM) in order to determine the relationship between these two important conditions. Method: 1066 participants of the Edinburgh Type 2 Diabetes Study, a large, randomly-selected population of patients with T2DM aged 60–75 years were invited for liver assessment. A range of liver disease markers (non-specific liver injury – serum alanine aminotransferase (ALT), aspartate aminotransferase (AST), gamma-glutamyl transferase (GGT); steatosis – liver ultrasound; steatohepatitis – serum cytokeratin-18; fibrosis – serum AST to Platelet Ratio Index (APRI), AST:ALT ratio, Enhanced Liver Fibrosis (ELF) panel, Fibrosis-4 Score, NAFLD Fibrosis Score; portal hypertension – platelet count) were measured. Subjects were followed-up using patient and GP questionnaires and record linkage for incident CV events (coronary artery disease (CAD), cerebrovascular disease and peripheral vascular disease). Results: At baseline there were 372/1035 patients with prevalent CVD, including 319/1035 with CAD. After mean follow-up of 4.4 years there were 121/1035 incident CVD events, including 76/121 CAD events. There were 30/82 CVD related deaths. However, risk of dying from or developing CVD was no higher in subjects with steatosis than without (HR 1.31 95% CI 0.78–2.20, p > 0.05). The only significant relationship was with GGT (U/L log2 incident CVD, adjusted HR 1.18 95% CI 1.00–1.39, p = 0.045; incident CAD, adjusted HR 1.24 95% CI 1.02–2.51, p = 0.032). Conclusion: We conducted the first comprehensive population-based study of older people with T2DM and found no association between non-invasive markers of hepatic steatosis, steatohepatitis, or fibrosis with the development of, or mortality from, CVD. Our finding of a significant independent association between GGT and CVD warrants further evaluation as a potentially useful addition to current CV risk prediction models in T2DM. Disclosure of interest: None Declared.